Psychiatric and cognitive function in patients with serotonin producing neuroendocrine tumors - Maryse J. Luijendijk; Margot E. T. Tesselaar; Huub H. van Rossum; Martijn van Faassen; Catharina M. Korse; Wieke H. M. Verbeek; Jocelyn R. Spruit; Pernilla C. Scheelings; Eva H. Hooghiemstra; Ido P. Kema; Henricus G. Ruhé; Sanne B. Schagen; et al. (Translational Psychiatry)
Abstract Cognitive and psychiatric problems are common in cancer patients, but literature on patients with neuroendocrine tumors (NET) is scarce. In a subset of these patients, the tumor produces serotonin, causing physical symptoms known as carcinoid syndrome. This peripheral overproduction of serotonin may cause central depletion of its precursor tryptophan, potentially resulting in cognitive and psychiatric problems. Therefore, we investigated cognitive and psychiatric function in patients with a serotonin overproduction and the association with this serotonin overproduction. Eighty-one patients with a serotonin-producing metastatic ileal NET underwent standardized neuropsychological and psychiatric assessment. Blood and urine samples were collected to determine concentrations of serotonin, its precursor tryptophan, and metabolite (5-HIAA). Multivariate normative comparison was applied to determine the prevalence of cognitive impairment. Separate linear regressions of serotonin, tryptophan, and 5-HIAA concentrations on cognitive function, depressive symptoms, and anxiety symptoms were performed, corrected for age, sex, education, and/or duration of illness. We found an 11% prevalence of cognitive impairment and a 20% prevalence of psychiatric disorders. Cognitive function was not related to measures of peripheral serotonin production. Unexpectedly, depressive symptoms were significantly associated with lower serum serotonin concentrations and elevated serum tryptophan concentrations. Cognitive symptoms of anxiety were also associated with elevated tryptophan concentrations. Concluding, cognitive or psychiatric problems occur in a minority of patients with NET and cannot be explained by tryptophan depletion following tumor-related serotonin production.